“Birds and Power Lines” in Russia: the USSR Heritage, Modern Achievements, and Issues - Elvira G. Nikolenko; Igor V. Karyakin (Пернатые хищники и их охрана)
We should begin to consider the issue of “Birds and power lines” in Russia with the state plan for the electrification of Russia, which was adopted in the USSR in 1920. The length of overhead power lines (PLs) had increased by several dozen times over ten years back then, but they were seated on wooden supports, which are pretty much safe for birds. The issue arose in the 1970s, with the adoption of the standard for PL on grounded reinforced concrete supports with pin insulators. Introduction of this standard led to the widespread bird mortality from electric shock.